Analisis Pengelolaan Sumber Daya Alam Pertanian Berbasis Kearifan Lokal Sebagai Upaya Pelestarian Lingkungan - Ardianti, Indah Marlina; Sania, Laelatus; Kuswanto, Eko; Alkausar, Triawan (ORGANISMS: JOURNAL OF BIOSCIENCES, 2023)
The majority of the population in Pekon Tegal Binangun are farmers who utilize land in the agriculture and plantation sectors. In managing their land, farmers strive to optimize yields. Natural resource management must be sustainable to ensure the preservation of environmental resources. The objective of this research is to determine whether the agricultural management system falls under sustainable agriculture and to understand the impact of locally wise agricultural resource management activities on environmental conservation efforts in Pekon Tegal Binangun. This study is a qualitative research conducted in the field. The subjects of the study are farmers in Pekon Tegal Binangun. The research data consist of primary and secondary data. The data analysis technique uses the Miles and Huberman Model. The analysis results indicate that the agricultural management system in Pekon Tegal Binangun still adheres to conventional agricultural practices and does not meet the organic farming indicators outlined in SNI 6729:2016 on Organic Farming.AbstrakMayoritas penduduk Pekon Tegal Binangun adalah petani yang memanfaatkan lahan dalam sektor pertanian dan perkebunan. Dalam pengelolaan petani memanfaatkan lahan dengan baik agar memperoleh hasil yang maksimal. Pengelolaan SDA harus keberkelanjutan agar sumber daya alam tetap terjaga. Tujuan penelitian ini untuk mengetahui sistem pengelolaan pertanian apakah termasuk sistem pertanian berkelanjutan dan mengetahui pengaruh kegiatan pengelolaan sumber daya alam pertanian berbasis kearifan lokal terhadap upaya pelestarian lingkungan di Pekon Tegal Binangun. Penelitian ini adalah penelitian kualitatif dengan jenis penelitian lapangan. Subjek penelitian ini adalah petani di Pekon Tegal Binangun. Data penelitian berupa data primer dan data sekunder. Teknik analisis data menggunakan Model Miles dan Huberman. Hasil analisis menunjukkan bahwa sistem pengelolaan pertanian yang ada di Pekon Tegal Binangun masih menerapkan sistem pertanian konvensional dan belum memenuhi indikator pertanian organik yang terdapat pada SNI 6729:2016 tentang Pertanian Organik